O Levenson’s Self Report Psychopathy Scale (LSRP) - Coelho, Luísa (2010)
Factorial Analysis (PCA) of the Portuguese version of Levenson’s Self Report Psychopathy Scale (LSRP-VP), with 19 items, reveals a two factors structure (F1 defined as primary psychopathy and F2 as secondary psychopathy), explaining respectively 21.56% and 14.63% of the variance. The model with two factors, tested via confirmatory factorial analysis, revealed a good fit with the observed data. Reliability (Cronbach alpha), data shows values of .81 for the total score, .82 for F1 and .73 for F2. This LSRP version shows also significant gender differences in primary psychopathy scale, with men scoring higher. This version requires further factorial validation studies.